2017
DOI: 10.3390/ijns3020012
|View full text |Cite
|
Sign up to set email alerts
|

Indifferent or Uninformed? Reflections of Health Professionals on Parental Education and Consent for Expanded Newborn Screening in Israel, 2008–2016

Abstract: Abstract:Background: This study explored the views of health professionals regarding parental education and informed consent for newborn screening (NBS) following the expansion of the NBS program in Israel. Methods: 24 in-depth interviews with 22 practitioners involved in NBS in Israel, and internationally, were conducted and analyzed qualitatively. Results and discussion: 1. Program creators, who were involved in the development, design, implementation, and delivery of the expanded NBS program, were concerned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Surveys in different countries have found that parents care more about the information on NBS than about their decision-making or consent options [ 39 , 40 , 41 , 42 ]. In contradiction to the screening criteria [ 21 , 22 , 34 ], some authors have advocated that screening for diagnoses with a clear direct benefit for the child (such as PKU, hypothyroidism, MCAD deficiency) can be mandatory or carried out without consent [ 43 , 44 , 45 , 46 , 47 ]. However, regardless of whether screening is mandatory (as in many US states [ 8 , 48 ]) or requires verbal or written parental consent (as in most European states [ 49 ] and in line with the screening criteria [ 21 , 22 , 34 ]), parental information is considered an essential part of NBS [ 46 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surveys in different countries have found that parents care more about the information on NBS than about their decision-making or consent options [ 39 , 40 , 41 , 42 ]. In contradiction to the screening criteria [ 21 , 22 , 34 ], some authors have advocated that screening for diagnoses with a clear direct benefit for the child (such as PKU, hypothyroidism, MCAD deficiency) can be mandatory or carried out without consent [ 43 , 44 , 45 , 46 , 47 ]. However, regardless of whether screening is mandatory (as in many US states [ 8 , 48 ]) or requires verbal or written parental consent (as in most European states [ 49 ] and in line with the screening criteria [ 21 , 22 , 34 ]), parental information is considered an essential part of NBS [ 46 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…A website with program information and secure screening results was launched in 2009. A study exploring the views of health professionals regarding parental education and informed consent for screening after expansion indicated a need for in-depth discussions and considerations regarding parental education, result communication, and informed consent processes for screening prior to any future program expansion [1345]. Following a successful pilot study and anticipating a high incidence because of consanguinity, NBS was expanded to include SCID.…”
mentioning
confidence: 99%